Blockchain Smart Contract in Supply Chain Financing - Denny Tenggino, Richman Pakpahan, Wendy Widjaya, Emil R. Kaburuan, Gunawan Wang, Sfenrianto (International Journal of Advanced Science and Technology, 2020)
Traditional supply chain financing has some disadvantages. Lack of trust, consuming time for making deal or agreement, payment, and many paperwork because many of this process is done manually and not provided by single system. This paper propose a new model supply chain financing using blockchain and smart contract in hopes to eliminates the current disadvantages that traditional supply chain financing has with make all the paper work move to digital platform so it will cut time more efficient and provide all the information in blockchain system that make it more open to all party that involved.